208 Long-term efficacy of erenumab in patients with chronic migraine who failed ≥3 prior prophylactic treatments. Issue 6 (27th May 2022) - Weatherall, Mark; Gantenbein, Andreas; Ritter, Shannon; Snellman, Josefin; Klatt, Jan Klatt; Mikol, Daniel
Abstract : Objective: Erenumab is a fully human monoclonal antibody. Following a 12-wk double-blind (DB), placebo- controlled chronic migraine (CM) study, a 52-wk open-label extension (OLE) study assessed long-term efficacy and safety of erenumab. We report the long-term efficacy of erenumab in a subgroup of patients in the OLE who failed ≥3 prior prophylactic treatments due to lack of efficacy and/or poor tolerability before enrolment in the parent study. Methods: During the 52-wk OLE patients received erenumab every 4wks. Following a protocol amendment, patients who had not reached wk28, had a dose increase to 140mg to allow them to receive the higher dose for ≥6 months; patients completing wk28 visit remained on 70mg throughout OLE. OLE treatment phase data were summarised by visit for all pts (combined treatment groups). Results: Of 605 pts enrolled in the OLE, 226 had ≥3 prior prophylactic TFs. Mean(SD) MMD at baseline for the TF subgroup was 18.95(4.2);overall, 18.11(4.5). At wk52, erenumab treatment resulted in a sustained reduction in MMD from baseline(TF, −7.94[6.5];overall, −9.29[6.6]) and 47% of pts in the ≥3 TF subgroup achieved ≥50% response. Conclusion: Erenumab treatment resulted in sustained efficacy in pts with ≥3 TF, a difficult-to-treat popula- tion, with greater efficacy for 140mg vs 70mg. 13m6ark.weatherall1@nhs.net